2021
DOI: 10.1080/14756366.2021.1916010
|View full text |Cite
|
Sign up to set email alerts
|

Tetralone derivatives are MIF tautomerase inhibitors and attenuate macrophage activation and amplify the hypothermic response in endotoxemic mice

Abstract: Macrophage migration inhibitory factor (MIF) is a pro-inflammatory cytokine playing crucial role in immunity. MIF exerts a unique tautomerase enzymatic activity that has relevance concerning its multiple functions and its small molecule inhibitors have been proven to block its pro-inflammatory effects. Here we demonstrate that some of the E-2-arylmethylene-1-tetralones and their heteroanalogues efficiently bind to MIF's active site and inhibit MIF tautomeric (enolase, ketolase activity) functions. A small set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…45,67 Because MIF often exerts its physiological effects in the form of a trimer, inhibiting the formation of MIF trimers can suppress MIF's biological activity. 68 CPSI-1306 precisely achieves this by disrupting the trimeric formation of MIF within the body, thereby inhibiting MIF's biological activity. 45 As a result, they reduce the binding of MIF trimers to CD74, inhibit various intracellular effects, interrupt its cascading amplification of inflammatory effects, and thus hinder the progression of IDD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45,67 Because MIF often exerts its physiological effects in the form of a trimer, inhibiting the formation of MIF trimers can suppress MIF's biological activity. 68 CPSI-1306 precisely achieves this by disrupting the trimeric formation of MIF within the body, thereby inhibiting MIF's biological activity. 45 As a result, they reduce the binding of MIF trimers to CD74, inhibit various intracellular effects, interrupt its cascading amplification of inflammatory effects, and thus hinder the progression of IDD.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to prevent and treat intervertebral disc degenerative diseases, we selected CPSI‐1306, a small‐molecular inhibitor with oral activity, which has been verified to treat a variety of inflammatory diseases and malignant tumors by inhibiting MIF and has achieved good effects 45,67 . Because MIF often exerts its physiological effects in the form of a trimer, inhibiting the formation of MIF trimers can suppress MIF's biological activity 68 . CPSI‐1306 precisely achieves this by disrupting the trimeric formation of MIF within the body, thereby inhibiting MIF's biological activity 45 .…”
Section: Discussionmentioning
confidence: 99%
“…As a fused ring, chroman-4-ones can be synthesized from some phenols [32,33]. The formed chroman-4-ones easily reacted with aldehydes for the preparation of (E)-3-benzylidenechroman-4-ones [34,35], and (E)-3-benzylidenechroman-4-ones can further participate in many reactions to produce various products, such as reduced product [36], cyclopropanes [37], cyclopentachromans [38], fivemembered heterocycles [39], six-membered heterocycles [40]. Therefore, chroman-4-ones can be used as the key raw material for the construction of polyheterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…MIF also promotes an important tautomerase activity (IUBMB Enzyme Nomenclature: EC 5.3.2.1) [48,49] by catalyzing the tautomeric keto-enol transformation of several substrates such as keto-phenyl-pyruvate to enol-phenyl-pyruvate and vice versa. Accordingly, the tautomeric activity can be divided into enolase and ketonase sub-activities [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we demonstrated that E-2-arylmethylene-1-tetralones and their heteroanalogues bind the active site of MIF and inhibit MIF tautomerase activity. The best selected inhibitor of the tetralone family with both ketonase and enolase inhibitory potential repressed ROS, nitrite and cytokine production, as well as NF-κB activation in LPS-induced macrophages, and regulated thermal alterations in an experimental model of systemic inflammation [51]. In our study, we identified a potent and selective tautomerase inhibitor, KRP-6 (Figure 2), which strongly inhibited MIF's ketonase (IC 50 = 4.31 ± 1.34 µmol/L) but failed to reduce its enolase activity (IC 50 = 1260 ± 159 µmol/L) [51].…”
Section: Introductionmentioning
confidence: 99%